ANALYSIS OF OUTPATIENT TREATMENT OF COMPLICATIONS OF DIABETES MELLITUS - TROPHIC ULCERS - Ushakov Sergey Nikolaevich; Rakhimov Azizjon Yakhyoyevich (Scholar Express Journals, 2023)
According to the World Health Organization, over the past 40 years, the number of adults with diabetes mellitus (DM) has increased from 108 million to more than 500 million. Diabetes disease and its prevalence have been growing sharply over the past decades. Diabetes mellitus is one of the ten leading causes of death worldwide and the number of its complications is steadily increasing. One of the main complications of diabetes mellitus is diabetic foot syndrome (DFS), a cause of non-traumatic amputations of the lower extremities. According to data, in 2020, diabetic foot syndrome develops in 6.3% of the total number of patients with diabetes. Due to the advent of new, modern methods of surgical and endovascular revascularization in developed countries, there has been a tendency to reduce the number of high amputations in patients with DFS, despite this, the relative number of other causes of amputation, primarily due to surgical infection of soft tissues, is increasing due to the development of various forms DDS - neuropathic, neuro-ischemic. In a large number of studies, the authors note late or insufficient diagnosis of this condition in patients with pathological changes in the foot due to diabetes, which leads to severe complications and is accompanied by a high risk of high limb amputation. In some sources, trophic ulcers complicate the course of the disease in 15%, in other sources, the authors note that trophic ulcers are the most common complication of diabetic foot syndrome, occurring in 50 - 60% of cases
Keywords: Diabetes mellitus; wound infection; ischemia; neuropathy